2014
DOI: 10.3109/02699052.2014.974672
|View full text |Cite
|
Sign up to set email alerts
|

Self-report prospective memory problems in people with stroke

Abstract: Results highlight the impact of PM failures in patients with stroke and their assessment, management and rehabilitation of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
(45 reference statements)
3
17
0
Order By: Relevance
“…Both found no significant differences between the report of significant-others and participants with stroke for total PM. However, when one of the studies (Man, Yip et al, 2015) examined the BADL and IADL subscales separately for both old- and young-stroke groups combined, a significant difference was found between scores for IADL PM, with significant-others reporting significantly more frequent PM failures for IADL (i.e., more non-routine) activities than the individuals with stroke.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Both found no significant differences between the report of significant-others and participants with stroke for total PM. However, when one of the studies (Man, Yip et al, 2015) examined the BADL and IADL subscales separately for both old- and young-stroke groups combined, a significant difference was found between scores for IADL PM, with significant-others reporting significantly more frequent PM failures for IADL (i.e., more non-routine) activities than the individuals with stroke.…”
Section: Resultsmentioning
confidence: 99%
“…Three of the studies that compared participants with stroke to controls reported that self-reported PM failures were not significantly different between the two groups (Barr, 2011; Brooks, Rose, Potter, Jayawardena, & Morling, 2004; Kim, Craik, Luo, & Ween, 2009). One study, however, reported differing results, concluding that individuals with stroke reported significantly more PM failures than controls (Man, Yip, Lee, Fleming & Shum, 2015). However, this finding was dependent on age, with older individuals with stroke, reporting more frequent PM failure than the younger control and older control groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The prefrontal lobes (particularly BA10) are activated during PM tasks (Burgess, Gonen-Yaacovi, & Volle, 2011). Everyday functioning is heavily reliant on PM abilities, and impairments in either type can influence one's ability to independently perform activities of daily living (Man, Yip, Lee, Fleming, & Shum, 2015). Changes in cognitive ability commonly occur after stroke .…”
mentioning
confidence: 99%